The Effect of Riddles Game Toward Student’s Vocabulary Mastery At The Eighth Grade of SMPN 1 Cihara Lebak Banten Academic Year 2023/2024 - Silviani, Nani; Rohimajaya, Nur Azmi; Novari, Ari Fajria (Journal of English Education Studies, 2023)
This research aims to investigate a significant Effect of Riddle Game Toward Student's Vocabulary Mastery at the Eighth Grade of SMPN 1 Cihara Lebak Banten in Academic Year 2023/2024. The research used the quantitative approach and quasi-experimental design. This research used two classes, they are control class and experimental class. The technique in choosing the sample is cluster random sampling, the researcher used VIII A (34 students) as experimental class and VIII B (33 students) as control class. The experimental group was taught by Riddle Game, while the control group was taught by Crassword Puzzle Game. In the technique Collecting of the data, the researcher gives pre-test and post-test. The score pre-test of control group are 2274, the score pre-test of experimental class are 2324. Then, the score post-test of control group are 2552, the score post-test of experimental group are 2842. In analyzing the data, the researcher used SPSS 25 statistical computation and used the result of the post-test both control class and experimental class to analyze the hypotheses test. The finding showed that the result of Significant two-tailed = 0.000 Therefore, the researcher concluded that the usage of Riddle Game has a significant impact on students vocabulary mastery in SMPN 1 Cihara Lebak Banten.